Pronominality of mutuality's field in Russian language - V K Radzikhovskaya (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2012)
The article presents pronominality as a founding of the functional-semantic mutuality's category. It is here established the displacement of opposite pronoun's paradigm on the plurality's context. Also it is shown forms specific to the semantic structure of this category in Russian language.